Analisis Ketepatan Kode Cedera dan Penyebab Luar Cedera pada RME Rawat Darurat di RSIJ Sukapura - Fazra Nanda; Deasy Rosmala Dewi; Noor Yulia; Bangga Agung Satrya (Lembaga Pengembangan Kinerja Dosen, 2025)
The accuracy of the diagnosis code is a statement that shows a code for a convincing diagnosis, and has been said to be certain and clear according to the ICD-10 guidelines. The purpose of this study was to obtain an overview of the analysis of the accuracy of injury codes and external causes of injury in emergency care electronic medical records at the Jakarta Islamic Hospital Sukapura. This research is descriptive research with a Mix Methode approach. Data collection techniques using observation and interview methods. Samples were taken using saturated sampling techniques totaling 81 electronic medical records of emergency care patients. The accuracy of the injury code is 22% correct, and the accuracy of the external cause of injury code incorporated in traffic accident cases and other accident cases is 0% correct. The low accuracy of injury codes was due to not adding character 5, block code errors, and errors in determining code categories. The results of the accuracy of the external cause of injury code obtained were 0% correct because 80 electronic medical records of emergency care patients did not contain the code for the external cause of injury. Factors that hinder the accuracy of injury codes and external causes of injury are influenced by man factors, namely high workload, dependence on ICD-10 codes on doctors, and lack of feedback audits. Then the influence of material factors, namely the incompleteness of supporting documents, lack of detail in diagnosis, and lack of chronological letters of events. Then the influence of method factors, namely unsupportive policies and procedures, lack of training and understanding, and weak application of external cause of injury codes.